Detergency Studies of Protease F1 - Thekkamalai, Gunasekaran (1996)
Protease F1, a thermostable alkaline protease extracted from Bacillus stearothermophilus strain F1 was investigated for its soil removing properties. In this study the general purity of crude Protease F1 was first determined. Protease F1 was found to be free of lipase, cellulase and a.-amylase activities. The washing performance of crude Protease F1 was measured in terms of percentage soil removal and compared to a commercial enzyme, Savinase. The effects of various factors such as types of soil, washing temperature, enzyme activity, water hardness, pH, types of surfactants and builders on the washing performance of Protease F1 were measured. The washing performance was determined by stirring a type of soiled cloths in 1 liter solution of enzyme (with a fixed amount of activity) for 10 minutes, followed by 2x3 minutes rinsing. The difference in the whiteness of the soiled cloth before and after washing indicate the degree of soil removal (or detergency). Among the various types of soiled cloth studied, the one soiled with oil, pigment and milk (AS12) gave a better contrast when washed by the enzymes than the cloihs soiled by btood or the egg. Protease Fl washed better than Savinase at an the temperatures studied. The difference in performance was found to be greatest at 70˚C. washing efficacy was found to increase with increase in concentration of the enzymes lUl1il a certain level beyond which a drop in the percentage soil removal was observed. The enzymes performed better at lower water hardnesses. Generally Protease F1 was more sensitive to water hardness than Savinase. At room temperature (RT) and 50˚C, Savinase performed better at all pH's. However, at 70°C and pH 7 and 8, Protease F1 performed better. When formulated with surfactants or builders, Protease Fl was found to enhance the performance of surfactants while Savinase, the builders. The best washing performance was when enzymes, surfactant and builders were formulated together and the washings carried out at RT and 50˚C.